2019
DOI: 10.1177/2631774519843400
|View full text |Cite
|
Sign up to set email alerts
|

Comparative outcomes of endoscopic ultrasound–guided cystogastrostomy for peripancreatic fluid collections: a systematic review and meta-analysis

Abstract: Background: Endoscopic ultrasound–guided cystogastrostomy has become the first-line treatment for symptomatic peripancreatic fluid collections. The aim of this study is to analyze the efficacy and safety of cystogastrostomy via a meta-analysis of the literature. Methods: We performed a systematic search of PubMed and Medline databases for studies published from January 2005 to May 2018. We included randomized controlled trials along with retrospective and prospective ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…On the other hand, the different techniques of LAMS deployment, treatment protocols and endoscopists with varying level of experiences might also be the reasons for the inconsistency with consideration of the heterogeneity of the previous studies. Another previously published meta-analysis conducted by Renelus et.al 12 included not merely mental stents, but also plastic stents, which has a confounding impact on the outcome of PFCs. The study from Varadarajulu et al 30 in favor of our ndings also showed clinical success was signi cantly higher for PPC and pancreatic abscess compared to WON.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the different techniques of LAMS deployment, treatment protocols and endoscopists with varying level of experiences might also be the reasons for the inconsistency with consideration of the heterogeneity of the previous studies. Another previously published meta-analysis conducted by Renelus et.al 12 included not merely mental stents, but also plastic stents, which has a confounding impact on the outcome of PFCs. The study from Varadarajulu et al 30 in favor of our ndings also showed clinical success was signi cantly higher for PPC and pancreatic abscess compared to WON.…”
Section: Discussionmentioning
confidence: 99%
“…However, a meta-analysis from Hammad et al published in 2018, aiming to compare the e cacy of LAMS drainage for PFCs with plastic stents, reported endoscopic LAMS drainage for WON has no difference with that of PPC 11 , meanwhile another meta-analysis from Renelus et al 12 included metal and plastic stents published in 2019 also supported this nding. With regard to the controversial results of stents in the management of PFCs, we have carried out a comparative study centering on the e cacy of LAMS for PPC and WON through a meta-analysis combined with a series of medical records from our medical center to evaluate the outcomes of different types of PFCs.…”
Section: Introductionmentioning
confidence: 97%
“…Overall, a recent systemic review and meta-analysis of outcomes related to endoscopic ultrasound-guided cystogastrostomy for pancreatic fluid collections by Renelus et al included seventeen studies involving 1,708 patients and reported the pooled adverse events rates for metal stents to be 14% and plastic stents to be 18% (76). Overall complications are rare and most can be managed successfully when recognized.…”
Section: Disadvantages and Complications Of Endoscopic Drainagementioning
confidence: 99%
“… 50 However, some researches suggest no significant difference in the clinical efficacy of endoscopy between PPC and WON. 18 , 37 , 51 However, inconsistencies in PFCs differentiation between endoscopists may have been responsible for these negative results. Petrone et al 52 reported that the adverse event rate in the WON group was higher than the PP group.…”
Section: Comparison Of the Clinical Efficacy Of Stents Between Pancrementioning
confidence: 99%